The RANK/ RANKL/ OPG interaction in the repair of autogenous bone grafts in female rats with estrogen deficiency - Tábata de Mello TERA; Renata Falchete do PRADO; Andrea Carvalho DE MARCO; Mauro Pedrine SANTAMARIA; Maria Aparecida Neves JARDINI (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The aim of this study was to evaluate the resorption process during the repair of autogenous bone grafts with or without coverage by an expanded polytetrafluoroethylene (e-PTFE) membrane in female rats with estrogen deficiency using the immunohistochemical technique. Eighty female rats were randomly divided into two groups (OVX and SHAM). The 40 female rats in the OVX group were subjected to ovariectomy, and the 40 female rats in the SHAM group were subjected to simulated ovariectomy. The two groups were further divided in subgroup E, which was subjected to surgery for placement of autogenous bone graft (ABG), and subgroup ME, in which the ABG was covered with an e-PTFE membrane. The animals were killed at 0, 7, 21, 45 and 60 days. The specimens were analyzed using immunohistochemistry for the bone resorption markers RANK, RANK-L and Osteoprotegerin (OPG). A higher remodeling rate was observed at 7 and 21 days after the autogenous bone grafts, when the markers were more intensely expressed. At the final time point, the specimens presented similar characteristics to those observed at the initial time point. The expression of immunohistochemical markers was not altered by the estrogen deficiency. The presence of the e-PTFE membrane delayed the bone resorption process, influencing the immunohistochemical expression of markers.